HRM Practices and its Impact on Customers’ Satisfaction of Pharmaceutical Companies in Nepal - Gautam, Tara Prashad (Nepal Journal of Multidisciplinary Research, 2021)
This paper aims to investigate the HRM practices and impact on Customers satisfaction in the pharmaceutical companies of Nepal A structured questionnaire was developed and distributed among 386 employees of 37 pharmaceuticals companies. Statistical correlation analysis was used to assess the impact of HRM practices on Customer satisfaction. The study reveals that employees in pharmaceutical companies are satisfied with the recruitment and selection, and training and development policy and practices of pharmaceutical companies. On the other hand, employees are dissatisfied with the human resource planning, working environment, compensation policy, performance appraisal, and industrial relations. The study suggests that the pharmaceutical companies should develop proper human resource policy and given emphasis on proper human resource practices to enhance the satisfaction of their customer and build them effective human resources.